Rooting of propagules of Arracacia xanthorrhiza Bancroft at the Colombian germplasm bank - Rosero Alpala, Maria Gladis (2023)
Introduction. The System of Germplasm Banks for Food and Agriculture of the Colombian Nation preserves roots and tubers of interest, such as Arracacia xanthorrhiza Bancroft. The renewal of the accessions allows to recognize the heterogeneity of the germplasm in rooting and development, shows differential groups, some with risk of survival and consequently risk of loss of genetic material. Objective. Determine the rooting potential of twenty-six accessions, belonging to the Arracacha Germplasm Bank. Materials and methods. The experiment was conducted at La Selva Research Center, Rionegro, Antioquia, Colombia, in 2019 - 2020. Twenty-six accessions were evaluated and the experiment was established with a completely randomized design under controlled conditions using water as propagation medium. A qualitative scale was defined and utilized to assess callus formation, while a quantitative scale was employed to evaluate the abundance of callus roots on exposed meristematic tissue. Results. Rhizogenesis began after twelve days with the formation of root meristematic tissue. Thirteen accessions had a high scale, two medium scale, and nine low scale. For the abundance and number of roots, nineteen accessions were located on a low scale, three on a medium scale, three in high scale including the control, and one accession was null. Using the logistic model, a growth rate (TC) of 0.74 and 0.51 mm/day was estimated for the accessions 15010099 and 15010097, while with the Gompertz model a TC of 0.39 mm/day for the accession 15010007. Conclusion. The rooting potential of A. xanthorrhiza was determined by attributes of precocity, abundance, and size of the roots in 26 accessions of the Germplasm Bank as a tool to generate actions in the conservation of accessions in the field.